2021
DOI: 10.1161/jaha.121.021245
|View full text |Cite
|
Sign up to set email alerts
|

Proteins as Mediators of the Association Between Diet Quality and Incident Cardiovascular Disease and All‐Cause Mortality: The Framingham Heart Study

Abstract: Background Biological mechanisms underlying the association of a healthy diet with chronic diseases remain unclear. Targeted proteomics may facilitate the understanding of mechanisms linking diet to chronic diseases. Methods and Results We examined 6360 participants (mean age 50 years; 54% women) in the Framingham Heart Study. The associations between diet and 71 cardiovascular disease (CVD)‐related proteins were examined using 3 diet qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A separate study examined the AHEI and modified versions of the Mediterranean-style Diet Score (mMDS) and mDASH in 6360 participants (mean age 50 years; 54% women) in the same Framingham Heart Study [ 22 ]. The proteomic analysis used a modified sandwich ELISA method multiplexed on a Luminex xMAP (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Resultsmentioning
confidence: 99%
“…A separate study examined the AHEI and modified versions of the Mediterranean-style Diet Score (mMDS) and mDASH in 6360 participants (mean age 50 years; 54% women) in the same Framingham Heart Study [ 22 ]. The proteomic analysis used a modified sandwich ELISA method multiplexed on a Luminex xMAP (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, higher B2MG was correlated with a higher occurrence of major adverse cardiac events [36]. And B2MG as a mediator had been linked to the diet and incident cardiovascular disease, also including all-cause mortality [37]. Lately, it was reported that circulating B2MG with higher levels could be a predictor for the progression of diabetic nephropathy in T2D patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…CD14 serves as a positive control as previous work demonstrates an association between sCD14 and dementia in FHS [4]. Details on protein biomarker measurement have been described in previous publications [27,28]. In brief, the proteins were measured by the Systems Approach to Biomarker Research (SABRe) that was established by the National Heart, Lung, and Blood Institute [27].…”
Section: Inflammatory Protein Biomarkersmentioning
confidence: 99%